Women as Initiators and Crafters of Human Growth in the ‘Reclaiming’ Witchcraft Tradition - Salomonsen, Jone (Pomegranate, 2002)
A substantial piece of Reclaiming’s initiation rite is inherted from the more ceremonial Witchcraft traditions and from privileged men’s secret societies at the turn of the 20th century. These traditions have all made the ’dying and rising god’ theme central to the rite.